Penerapan Teknologi GPS Tracker Untuk Identifikasi Kondisi Traffik Jalan Raya - Widyantara, IM. O.; Warmayana, I G.A.K.; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i01p07)
Real time tracking system technology has been made possible by integrating three technologies, namely global positioning system (GPS), database technologies such as geographic information system (GIS) and mobile telecommunications technologies such as general packet radio service (GPRS). This paper has proposed a vehicle tracking mechanism based on GPS tracker to build a real-time traffic information system. A GPS server is built to process data of position and speed of the vehicle for further processed into vehicle traffic information. The Server and GPS tracker is designed to communicate using GPRS services in real time. Furthermore, the server processes the data from the GPS tracker into traffic information such as traffic jam, dense, medium and smoothly. Test results showed that the GPS server is able to visualize the real position of the vehicle and is able to decide the category of traffic information in real time.
Keywords: GPS, GIS, GPRS, Traffik road